Age Maturity of Female Japanese Quails Fed Diets Containing Katuk Leave Meal (Sauropus androgynus L.Merr. - Wiradimadja, R; Piliang, WG; Suhartono, MT; Manalu, W (ANIMAL PRODUCTION, 2007)
This experiment was conducted to study the effects of katuk leave meal on sexual maturity in Japanese quail.  Three hundred female Japanese quails, with 4 weeks age, were assigned into a completely randomized design with 4 treatments i.e., R1 (diet with neither katuk leave meal nor cholesterin), R2 (diet without   katuk leave meal + 0.10% cholesterin), R3 (diet with 15% katuk leave meal without cholesterin), and R4 (diet with 15% katuk leave meal + 0.10% cholesterin). The parameters measured were estradiol hormone in plasma, and age maturity (five percent henday production). Estradiol hormone was measured with Radioimmunoassay. The data were collected and analyzed by using completely randomized design. The results showed that the addition of 15% katuk leave meal in the diet significantly decreased the estrogen concentration (P<0.05), so that slow down on the age maturity of female Japanese quail. (Animal Production 9(2): 67-72 (2007)  Key Words : Katuk leave meal, estradiol hormone, age maturity, quail